ANALISIS PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA APARATUR KANTOR CAMAT TANJUNG REDEB KABUPATEN BERAU: ANALISIS PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA APARATUR KANTOR CAMAT TANJUNG REDEB KABUPATEN BERAU - Dandy Ahmad Drajat (ECO-BUILD, 2022)
The writing is left of a theoretical framework, the idea of the experts, or the understanding of researchers based on their experiences, and then developed into the problems and their solutions - Solution proposed to obtain justification (verification) in the form of data support emperis field. This study aims to identify and Analysis Of The Influence Of Education And Training On The Performance Of The Sub Tanjung Rebab District Berau, The method used in this study is a quantitative method, with a population of as many as 30, a sample of 30 people and data analysis techniques to test the validity of the research instrument, reliability testing and using multiple linear regression. The results of this study indicate that the motivation, Education And Training variables in itself - its own effect on the toward Performance The Performance Of The Sub Tanjung Rebab District Berau, While variable Employee Education is a dominant variable affecting the toward The Performance Of The Sub Tanjung Rebab District Berau, Meanwhile, based on the F test at level α of 5% prove all independent variables had a significant effect on the dependent variable together (simultaneously). Adjusted determination (R2) is 0.810 or 81%, showing the contribution given all independent variables to the dependent variable.